El sujeto y el lazo social en el Psicoanálisis (2011)
ABSTRACT: Psychology becomes equivalent the notion of subject, person, individual, and the ego; and it defines its nature according to his/her gregarious condition: there are not any formal difference and its terms are used indiscriminately. There is a clear difference between the ego and the subject in psychoanalysis, this difference belongs to Freudi-an's definition of the decomposition of the psychi-cal personality; it also questions the psychological notion of personality representative unit. Social fabric in psychoanalysis is defined on discursive terms and it does not make difference between individual subject and social subject, meanwhile the speech regulates the enjoyment in every social fabric where subject is registered.